Perancangan Website Desa Wisata Claket Pacet Mojokerto Sebagai Media Informasi Dan Promosi: Perancangan Website Desa Wisata Claket Pacet Mojokerto Sebagai Media Informasi Dan Promosi - Novan Andrianto (Yayasan Pendidikan Penelitian Pengabdian Algero, 2024)
This article delves into the in-depth design and development of the official website for Claket Tourist Village in Pacet, Mojokerto, accessible through www.desawisataclaket.com. Recognized as a crucial component in advancing and communicating the tourism destination, the website plays a pivotal role. Its design process involves the application of Design Thinking, with a primary focus on user experience. The main objective of this website is to provide comprehensive information about tourist attractions, local cultural richness, accommodation options, culinary delights, and cultural event schedules in Claket Tourist Village. Through a creative approach, appropriate color usage, and tailored font types, the website aims to be a highly effective tool in introducing Claket Tourist Village to potential visitors. More than just an information platform, the website is considered a bridge connecting visitors to the natural and cultural heritage of Claket Tourist Village. Therefore, it not only delivers positive benefits to visitors but also contributes positively to the local community. Consequently, it is anticipated that support for the development of the tourism sector in the region will increase, creating sustained positive impacts for Claket Tourist Village and its residents.